2018
DOI: 10.1097/md.0000000000009831
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous papillary thyroid cancer and non-Hodgkin lymphoma

Abstract: Rationale:Differentiated thyroid cancer is the most common endocrine malignancy with concomitant hematological malignancy in 7%.Patient concerns:We present a case of a synchronous papillary thyroid cancer and a follicular variant of non-Hodgkin lymphoma and discuss the possible diagnostic and treatment dilemmas.Diagnosis:A 48-year-old female was reffered to our hospital with diagnosis „thyroid cancer“. Due to a history compatable of synchronous lymphoproliferative disease we performed a computed tomography, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
3
9
0
Order By: Relevance
“…We found only 2 cases reporting simultaneous PTC and non-Hodgkin lymphoma and 2 cases with simultaneous PTC and HL. [1215] Pianovski in 2004 [14] reported HL was presented as a rapidly enlarging supraclavicular nodule 30 days after a total thyroidectomy in a teenager and Rizkallah et al [15] in 2014 reported a case of HL presenting as typical B symptoms incidentally diagnosed with PTC by mediastinoscopy in a young man. Both of them had no molecular analysis of PTC and were little different from our case; the occurrence of PTC an HL was presented as a suspicious thyroid nodule and enlarged cervical lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found only 2 cases reporting simultaneous PTC and non-Hodgkin lymphoma and 2 cases with simultaneous PTC and HL. [1215] Pianovski in 2004 [14] reported HL was presented as a rapidly enlarging supraclavicular nodule 30 days after a total thyroidectomy in a teenager and Rizkallah et al [15] in 2014 reported a case of HL presenting as typical B symptoms incidentally diagnosed with PTC by mediastinoscopy in a young man. Both of them had no molecular analysis of PTC and were little different from our case; the occurrence of PTC an HL was presented as a suspicious thyroid nodule and enlarged cervical lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we agreed that the “lymphoma first approach” was recommended for the synchronized condition. [8,12] In this patient, we started the chemotherapy of HL after total thyroidectomy. It is noted that patients received HL treatment are at increased risk of secondary neoplasms, specifically thyroid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Both tumors share a high level of aggressiveness that contributed to the grave prognosis seen in our case. On the other hand, the type of nodal marginal zone NHL that was associated synchronously with thyroid papillary cancer has not been described previously [11]. Moreover, although the colon is a common site of involvement in synchronous MPMs, its association with retroperitoneal Hodgkin lymphoma has never been seen previously either according to our literature review.…”
Section: Discussionmentioning
confidence: 53%
“…According to our review of literature, some studies reported that subtotal thyroidectomy followed by radioiodine use without total thyroidectomy and lymphadenectomy would be an alternative option [7]. Georgi et al and colleagues [3], reported a similar case with different management, they first started with chemotherapy of lymphoma and then went for a total thyroidectomy. Up to this time there's no exact sequence of treatment of synchronous papillary thyroid cancer and Hodgkin lymphoma, that's due to its rarity and the scanty literature available.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of papillary cancer has raised reaching 7.7 per 100.000. Most are detected in the early subclinical stage, concluding that the actual numbers did not increase it's just that the disease is being detected earlier [3]. When the second primary malignancy is detected in less than 6 months from the index tumor the term synchronous is implied.…”
Section: Discussionmentioning
confidence: 99%